2015
DOI: 10.1371/journal.pone.0124667
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Burkholderia pseudomallei Strains Using a Murine Intraperitoneal Infection Model and In Vitro Macrophage Assays

Abstract: Burkholderia pseudomallei, the etiologic agent of melioidosis, is a gram-negative facultative intracellular bacterium. This bacterium is endemic in Southeast Asia and Northern Australia and can infect humans and animals by several routes. It has also been estimated to present a considerable risk as a potential biothreat agent. There are currently no effective vaccines for B. pseudomallei, and antibiotic treatment can be hampered by nonspecific symptomology, the high incidence of naturally occurring antibiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(105 citation statements)
references
References 92 publications
6
97
0
2
Order By: Relevance
“…In the initial survival study, there were 10 mice per group with 5 groups challenged IP with different amounts of each strain that were quantified via OD 620 estimations. The IP 21 day LD 50 for Bp 1106a and Bp HBPUB10134a were approximately 42,000 colony forming units (CFU) and 10 CFU, respectively, and had been reported previously [22]. In the early host innate response study approximately 6 LD 50 equivalents of each strain was delivered IP to each mouse in 200 ml of GTB.…”
Section: Animal Challengessupporting
confidence: 59%
See 3 more Smart Citations
“…In the initial survival study, there were 10 mice per group with 5 groups challenged IP with different amounts of each strain that were quantified via OD 620 estimations. The IP 21 day LD 50 for Bp 1106a and Bp HBPUB10134a were approximately 42,000 colony forming units (CFU) and 10 CFU, respectively, and had been reported previously [22]. In the early host innate response study approximately 6 LD 50 equivalents of each strain was delivered IP to each mouse in 200 ml of GTB.…”
Section: Animal Challengessupporting
confidence: 59%
“…It is unclear if this was a true relapse or possible reinfection [24,25]. Bp HBPUB10134a was isolated from a tracheal suction specimen in 2010 [22]; April Shea, USAMRIID, personnel communication. In addition to the significantly different clinical origins of these two strains, Bp HBPUB10134a and Bp 1106a exhibited differences in their virulence/pathogenicity in BALB/c mice, as shown in Fig.…”
Section: Clinical Source and Pathogenicity Of B Pseudomallei Hbpub10mentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical manifestations of the disease vary from acute septicemia to chronic infection (88% and 12% of cases in Australia, respectively) (24). Intracellular survival and cell-to-cell spread may have contributed to the organism's ability to evade the immune response, causing a persistent infection (26). The Darwin prospective melioidosis study examined 540 cases of culture-confirmed melioidosis from the Top End of Australia between 1989 and 2009 and identified pneumonia as the most common clinical manifestation (51%, 278 cases), followed by genitourinary infection (14%), skin infection (13%), bacteremia without evident focus (11%), septic arthritis or osteomyelitis (4%), and neurological melioidosis (meningoencephalitis, myelitis, and cerebral abscesses, 3%) (27).…”
Section: Clinical Presentationmentioning
confidence: 99%